933 Piloting of a social marketing campaign to reduce musculoskeletal risks related to manual materials handling on construction projects. (24th April 2018) - Dale, AM; Betit, E; Strand, J; Schneider, S; Cain, C; Rempel, D
Abstract : Introduction: Musculoskeletal disorders (MSD) are the most common work-related health issue among construction workers. Despite the existence of practical solutions for reducing physical exposures, prevention efforts to reduce MSDs have not been systematically adopted by most construction employers. This study will describe a social marketing campaign to promote ergonomic methods in construction safety. Methods: The Ergonomics Community of Practice, consisting of researchers, industry stakeholders, and insurance industry representatives, has developed a Pilot Ergonomics Social Marketing Program to promote safer Manual Materials Handling (MMH) on construction sites. The work group recognised a need for contractor engagement in planning for safer MMH with an emphasis on; establish weight limits for lifting; and storing materials to reduce MMH risks. Formative work with construction contractors explored how contractors approached planning and three MMH practices. Program materials will be based on formative work results. Results: Data from 81 surveys with construction contractors showed most considered themselves knowledgeable about ergonomic hazards (85%) and knew how to prevent them (79%). Most contractors (57%) reported using planning strategies to prevent MMH risks both before and during project work but others reported little or no planning. Interviews of 12 'positive deviant' contractors identified planning for MMH as a common practice, and produced descriptions of several strategies used to overcome barriers for MMH activities. Discussion: The development of social marketing campaign materials are based on effective MMH strategies that have been adopted by proactive contractors. These materials, including a planning tool, will be tested by intermediary organisations (insurers and construction organisations) with contractors. The social marketing process and preliminary result on the number of contractors who chose to implement the program, the degree the program was implemented, and whether the implementation was sustained during the pilot period will be covered in this presentation.